Efficacy of initial haemopurification strategy for acute paraquat poisoning in adults: study protocol for a randomised controlled trial (HeSAPP). Issue 6 (22nd June 2018) - Cui, Jian-Wei; Xu, Yinyan; Wang, Yibo; Gao, Yan-Xia; Guo, Shigong; Wang, Meng; Lu, Xin; Yu, Shiyuan; Ma, Yong; Yuan, Ding; Che, Lu; Sun, Pei; et al.
Abstract : Introduction: Paraquat (PQ) is a widely used herbicide which is inexpensive and easily accessible for people in rural areas. A small amount of PQ ingestion could be lethal, yet currently, the optimal treatment is still controversial. Extracorporeal therapies (ECTR) have been practised in PQ poisoning management, though limited evidence could be obtained to suggest its superiority over conservative therapy. Haemodialysis (HD) and haemoperfusion (HP) are most commonly used, while some institutions also choose HP–HD concurrent therapy. The object of the present trial is to investigate whether haemopurification therapy can reduce mortality compared with conservative therapy. Methods and analysis: This is a planned single-centre, non-blinded, randomised controlled trial. Acute PQ poisoned adults who have orally ingested PQ within 24 hours would be recruited. A total of 360 patients would be recruited and randomly assigned to four groups, that is, HP, HD, concurrent HP–HD and control, at a 1:1:1:1 ratio. Subjects would be also stratified by their urine dithionite test results. Primary outcome is 28-day all-cause mortality. Secondary outcomes include survival time, all-cause mortality at the 3rd, 7th and 60th day, rate of major complications, Acute Physiologic and Chronic Health Evaluation score and Poisoning Severity Score, etc. Ethics and dissemination: The protocol and informed consent documents have been approved by the Ethics Committee of The First Affiliated Hospital of Zhengzhou University in September 2017 (approval number: 2017-KY-10). The result of this trial would be submitted to peer-reviewed journal. Trial registration number: NCT03314909 ; Pre-results.